Teks dan Konteks Kitab Hadis Melayu Pertama: Studi atas Naskah Hidayat al-Habib Karya al-Raniri - Alimron Alimron (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2018)
This is a study of Hida>yat al-H{abib's text, the first Malay hadi>th book of Nuruddin al-Raniri. This study aims to describe Hidayat al-Habib's text, present its text edits and understand its contents, and understand its contextuality in the traditions of the hadith in Nusantara. Hidayat al-Habib's texts contain a collection of hadiths of the Prophet Muhammad which consists of 53 chapters in which contains the hadiths on the recommendation of the good deed (targhib) and the threat for the bad deed (tarhib), which thematically can be grouped into three major themes, which are related to the morality to Allah and His prophets, morality to other people, and morality to the own self (personality), with the total number of hadits about 831 hadiths. Contextually, with this work al-Raniri wants to explain comprehensively the guidelines and guidance that the Prophet Saw. taught related to several aspects of life to Muslims, considering the people of the Nusantara at that time despite embracing Islam but in everyday reality there are many who apply various patterns of life and customs that are not in accordance with the Islamic Shari'ah.Â